Pengaruh Beban Kerja dan Stres Kerja Terhadap Kepuasan Kerja Pada PT XYZ - Erlina Eka Sulistyowati; Purwatiningsih, Purwatiningsih; Ratih Setyo Rini (Institut Teknologi dan Bisnis (ITB) Semarang, 2024)
This research aims to determine the effect of workload and work stress on job satisfaction at PT XYZ. The method used is a quantitative method. The subjects of this study are 47 employees of PT XYZ Jakarta Centrum Main Branch Office. The data analysis techniques used include Data Quality Test, Classical Assumption Test, Hypothesis Test, Multiple Regression Analysis, and Determination Coefficient Test using IBM SPSS 25 software. The results of this study indicate that partially, workload has a positive and significant effect on job satisfaction. This is indicated by a significance value of 0.015 < 0.05 and a t-value > t-table (2.536 > 2.015). Partially, work stress does not have a positive and significant effect on job satisfaction, as evidenced by a significance value of 0.729 > 0.05 and a t-value < t-table (0.348 < 2.015). Based on the F-test results, workload and work stress do not have a positive and significant effect on job satisfaction simultaneously. This is evidenced by a significance value of 0.052 > 0.05 and an F-value < F-table (3.175 < 3.20).